2017
DOI: 10.1177/0016986217722616
|View full text |Cite
|
Sign up to set email alerts
|

Online Teacher Professional Development for Gifted Education: Examining the Impact of a New Pedagogical Model

Abstract: This article theoretically develops and examines the outcomes of a pilot study that evaluates the PACKaGE Model of online Teacher Professional Development (the Model). The Model was created to facilitate positive pedagogical change within gifted education teachers’ practice, attitude, collaboration, content knowledge, and goal effectiveness. Kirkpatrick and Kirkpatrick’s model of training evaluation suggests that trainees should evaluate the training for satisfaction at the time the training is completed, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
(55 reference statements)
1
18
0
2
Order By: Relevance
“…In our study, organizational and pedagogical conditions reflect the totality of measures aimed at improving the training of teachers for working with gifted students. The organizational and pedagogical conditions for preparing teachers for work with gifted students were determined with the analysis of the scientific literature on teacher education both domestic (Igropulo, Semina, Sorokopud, & Shapovalov, 2013;Igropulo, Magomedov, & Romaeva, 2018;Vezirov, Borozinets, & Sorokopud, 2013 ) and foreign authors (Edinger, 2017;Hertzog, 2017;Kettler, Oveross, & Bishop, 2017;Rowan & Townend, 2016). First of all, it should be noted the importance of organizational and methodological events, which includes the creation of a database of teachers who have trained schoolchildren -winners and prize-winners of Olympiads; the creation and operation of the "Preparing for the Olympiads" section on the https://doi.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, organizational and pedagogical conditions reflect the totality of measures aimed at improving the training of teachers for working with gifted students. The organizational and pedagogical conditions for preparing teachers for work with gifted students were determined with the analysis of the scientific literature on teacher education both domestic (Igropulo, Semina, Sorokopud, & Shapovalov, 2013;Igropulo, Magomedov, & Romaeva, 2018;Vezirov, Borozinets, & Sorokopud, 2013 ) and foreign authors (Edinger, 2017;Hertzog, 2017;Kettler, Oveross, & Bishop, 2017;Rowan & Townend, 2016). First of all, it should be noted the importance of organizational and methodological events, which includes the creation of a database of teachers who have trained schoolchildren -winners and prize-winners of Olympiads; the creation and operation of the "Preparing for the Olympiads" section on the https://doi.…”
Section: Resultsmentioning
confidence: 99%
“…The following section examines gifted education’s practice-based elements of instructional learning design as they pertain to the instructional learning design in Edinger’s (2017) PACKaGE model. The following oTPD elements, evaluated by teachers for usefulness and increased understanding of elements of instructional learning design for gifted education, are described below.…”
Section: Instructional Learning Designmentioning
confidence: 99%
“…A 2017 pilot study found that the PACKaGE model of oTPD for gifted education encouraged positive pedagogical change within gifted education teachers’ p ractice, a ttitude, c ollaboration, content k nowledge, a nd g oal e ffectiveness (Edinger, 2017). Beginning in 2008, the PACKaGE model was used to design six oTPD courses in gifted education with topics including gifted education perspectives, curriculum, social/emotional needs, differentiation, special populations, and an introduction to the gifted education field.…”
mentioning
confidence: 99%
“…Although professional development is a necessary component of all educational improvement efforts (Guskey, 2000), research on its effectiveness indicates mixed results. Some studies suggest that sustained, content-focused professional development can increase teacher knowledge (Clair & Adger, 2000;Yuen et al, 2018) and change teacher practice (Desimone, Porter, Garet, Yoon, & Birman, 2002;Edinger, 2017;Garet, Porter, Desimone, Birman, & Yoon, 2001) in ways that ultimately improve student learning (Saxe, Gearhart, & Nasir, 2001). Yet others suggest that professional development does not create effective or sustainable change in teacher practice (Clair & Adger, 2000;Peters & Jolly, 2018;Petty, Heafner, Farinde, & Plaisance, 2015), or impact student achievement (Darling-Hammond & Berry, 2006).…”
Section: Professional Developmentmentioning
confidence: 99%